The overtures of Daniel-Francois-Esprit Auber - Auber, D. F. E.; Letellier, Robert Ignatius (Cambridge Scholars, 2011)
The overtures of Daniel-François-Esprit Auber (1782-1871), once as popular as those of Gioacchino Rossini and Franz von Suppé, were formerly known everywhere, a staple of the light Classical repertoire. The influence of Auber's melodies and dance rhythms on piano and instrumental music, and on the genre of Romantic comic opera, especially in Germany, was overwhelming. The operas themselves, apart from Fra Diavolo (1830), have virtually passed out of the repertoire, but some of their overtures...
Keywords: Overtures (Piano), Arranged; Overtures : Scores